2012
DOI: 10.1007/s11627-012-9442-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of explant age, germination medium, pre-culture parameters, inoculation medium, pH, washing medium, and selection regime on Agrobacterium-mediated transformation of tomato

Abstract: An efficient protocol was developed for Agrobacterium tumefaciens-mediated transformation of tomato (Solanum lycopersicum) cultivars using cotyledon explants. The transformation frequency was assessed in response to several different factors, including seed germination medium, seedling age, pre-culture duration, pre-culture and cocultivation media, inoculation medium, medium pH, washing medium, and kanamycin concentration in initial selection medium. Cotyledons excised from 6-d-old seedlings germinated on half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 59 publications
(92 reference statements)
2
36
0
1
Order By: Relevance
“…The pre-culture period increases the regeneration percentage by eliminating the hypersensitive response of explants induced by Agrobacterium in co-cultivation stage (Arcos-Ortega et al, 2010). The pre-culture period is an important factor that significantly affects the TE in tomato (Rai et al, 2012). TE is closely linked with cell division or dedifferentiation (Arias et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pre-culture period increases the regeneration percentage by eliminating the hypersensitive response of explants induced by Agrobacterium in co-cultivation stage (Arcos-Ortega et al, 2010). The pre-culture period is an important factor that significantly affects the TE in tomato (Rai et al, 2012). TE is closely linked with cell division or dedifferentiation (Arias et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These differences might be due to difference in Agrobacterium strain, type and age of explants and genotypes. Rai et al (2012) optimized an efficient Agrobacterium-mediated transformation protocol for tomato cultivars using cotyledons explants and reported that six days pre-culturing period significantly improved the TE upto 44.3% in tomato. Similarly, Duan et al (2010) conducted a study on tomato cv.…”
Section: Discussionmentioning
confidence: 99%
“…Putative transformants were obtained by co-culturing the explants with A. rhizogenes for 0-3 d. After 12 d of culture (Table 1), the hairy root started appearing from wounded sites of explants co-cultured for 3 d with both the bacterial strains ( Figure 1A and B), while in other explants co-cultured for 0 and 2 d, the hairy root appeared after more than 12 d. The increase in the co-culture period ensures the rapid transformation of cells infected by the bacteria, which allowed the induction of hairy roots within less time (Rai et al 2012). Both the A. rhizogenes strains used in our study showed a good transformation frequency (Table 1).…”
Section: Induction Of C Roseus Hairy Rootsmentioning
confidence: 97%
“…Pada eksplan tanaman tomat yang tidak diinduksi, transformasi gen terjadi hanya 0,45% sedangkan bila diinduksi selama 2 hari, efisiensi transformasi meningkat menjadi 6,32% (Rai et al 2012). Eksplan yang diinduksi dapat mengaktifkan pembelahan sel sehingga dapat meningkatkan transformasi.…”
Section: Transformasi Nilam Dengan Gen Oswrky76 Melalui Agrobacteriumunclassified